Research on Evolutionary Game of Adopting Blockchain-Based Automotive Traceability - Xiaoyu Tang; Shouwei Li; Jingwei Li; Yonghong Zhang (Information, 2024)
To adopt the blockchain-based automobile traceability system (BCATS) and increase the transparency of the Chinese auto market, this study constructs a tripartite evolutionary game model of manufacturers, regulators, and consumers, discusses the evolutionary stabilization strategy (ESS) under different cases, and analyzes the influencing factors on the tripartite ESS through numerical simulation. The study finds that there exists an ESS of blockchain adoption and tripartite cooperation, and it is influenced by different factors including blockchain construction cost, traceability service price, and government subsidy. Lowering the blockchain construction cost, and increasing the traceability service price and government subsidy can all have a positive impact on accomplishing the ideal ESS, but the latter two can also have a negative impact when they are beyond the scope of effectiveness. The study results provide practical recommendations for adopting blockchain in the auto traceability, which can help to promote blockchain in the Chinese auto market.